Video Documentation on Forgotten Forest Installation - Auzani Zeda, Mohamed Kassim; Endang, Lestari (Vimeo, 2019)
Forgotten Forest emerged as a collaboration work to express both artists’ passion about ‘Alam’. The work was inspired by the massive development issues the tropical rainforest ecosystems in Borneo and other parts of the world are facing. It quest is about the human relationship of love and harmony with the natural world, something that deep down human nature yearns for. It highlights the loss of nature in the urban landscape and points out humankind's loss of its primal bonds with the natural world.